On the problem of adopting pragmatism in public administration - Snider, Keith F. (2011)
Answering the question, "Should public administration adopt pragmatism?" requires some agreement on what pragmatism means and what that adoption might entail. This article argues that such agreement does not currently exist and, without it, calls by administrative theorists for adoption will not receive their intended responses. - Reproduced.
Keywords: Public administration